Digital Technology Application In Project Management - Teo, Nigel Cheng Long (2021)
Digital technology has grown rapidly in today world and enhanced the quality of life, and digital technology has provided fast ways to communicate through instant messaging apps and social media platforms, technological. Due to growing challenges in today's technology-enabled work environment, where digital technology tools are frequently used for collaboration, communication, and implementation of project management methods, technology assumes prominence in the context of project management. Even co-located project teams are increasingly turning to the digital technology for these goals. This study aims to explore further info and perception on application of digital technology in project management, and how digital technology can be incorporated effectively in project management. Specifically, it investigated on how digital technology able to assist project manager and facilitate project progress and efficiency. The published literature has indicated that by applying digital technology in project management has facilitate the process and improve the project efficiency. To gather information, seven interview sessions were conducted. All seven respondents worked in different industries, inclusive of oil and gas, manufacturing, trading, and, of course, M&E. Meanwhile, every respondent had more than 5 years of project management experience, with the longest being 20 years. The results revealed that the majority of respondents used digital technology in project management because it was convenient, time saving, and reduced hassle, among other things. For example, information can be quickly disseminated among project team members, scheduling purposes, meeting scheduling, and so on. Data saturation was used to discover all major findings, as data saturation was achieved when there was no more information to be collected from the respondents. The results suggest that most organisations are adopting digital transformation as it improves communication, collaboration, VI and content management not just within an organisation, but also in project management. Meanwhile, most projects could not be completed physically during the pandemic, thus digital technology was used to address to the situation.